Prognostic Factors after Liver Resection for Colorectal Liver Metastasis - Matias, Margarida (2015)
Introduction: Surgery is the only potentially curative treatment for patients with colorectal liver metastases, resulting in 5-year survival rates of 36–58%. Although many studies have been performed to determine prognostic factors for tumor recurrence and survival after resection of colorectal liver metastases, there are few prognostic scoring systems stratifying patients undergoing surgery for colorectal liver metastases into risk group models.Objectives: To identify, evaluate and compare the existing prognostic scores for survival after surgery for resection of colorectal liver metastases.Material and Methods: Electronic search in PubMed, Cochrane and Embase from 1990 to 2013 using the terms ‘hepatic resection’, ‘colorectal cancer’, ‘liver metastasis’, ‘hepatectomy’, ‘prognostic’, and ‘score‘. Only studies proposing a prognostic model or risk stratification based on clinical and/or pathological variables were included.Results: From 1996 to June 2013, 19 scoring systems were identified, including one nomogram. Thirty prognostic factors were identified although none of the factors was common to all prognostic models. The 4 factors most often included were: number of liver metastases, regional lymph node metastization of primary tumor, preoperative CEA level and maximum size of metastases. The median study sample size was 305 patients (81-1 568 patients) and median follow-up was 33 months (16-54 months). All studies were retrospective and used the Cox proportional hazards model for multi-variable analysis.Conclusion: Several factors have been constantly reported as having prognostic value after liver resection of colorectal livermetastases, although there is no consensus on the ideal scoring system.